(untitled) (diségno, 2021)
Architectural drawing, as part of a means of communication can be understood as the signifier that contains or refers to a series of images and ideas that serve as a referent and that have been, in any case, organized by the author of the drawing. This relationship will not be by definition univocal but, although following different degrees of ambiguity, it will have to be constructed, again and again, for each reader. The interpretation of this graphic signifier, its use in language, will be an essential mental exercise during the analysis of the graphic and will be directly related to the process of drawing that has been carried out and which, in any case, always requires temporality. This research work is based on the hypothesis that the reader must carry out an exercise that is almost as important as the author during a process that, as such, involves time and, furthermore, requires reversibility for its achievement. Based on this idea, the relationship (and therefore the distance) between the eye that reads and the hand that draws is analysed. The theoretical approach is accompanied by practical examples to help understand the method developed, based on reversibility as a tool for constructing the graphic image. It is this journey “backwards” by means of which we are able to end up analysing, valuing and, in short, constructing the graphic criterion with which to evaluate architectural drawing.